Atividades Curriculares de Integração Ensino, Pesquisa e Extensão (ACIEPEs) como estratégia de formação continuada : um estudo de caso com formação matemática de professores polivalentes no Município de São Carlos - Curilla, Rosemeire Aparecida Trebi (2016)
This research had as its general objective to discuss the contributions of the Curricular Activities of Integration Teaching, Research and Extension (ACIEPEs) offered by the Federal University of São Carlos (UFSCar) for the training of teachers promoted by this IES and for the professional development of teachers of Basic Education. It had as its specific objectives: to investigate the relationship between the ACIEPEs’ offer, and the demand regarding the training needs of the teachers who work in the Initial Years of Elementary School; To investigate the contributions of ACIEPE "Information Technology in the Training and Performance of Teachers Teaching Mathematics in the Beginning Years" for the professional activity and the pedagogical practice of teachers who attended it; and to offer subsidies to the Center for Teacher Education (NFP) of UFSCar to aggregate and streamline the ACIEPEs focused on teacher education. Starting from the propositions in the scope of teacher training, (a) ACIEPEs are activities that promote the articulation between the initial and continuing teacher training, considered by scholars in the area of education as primordial for the effectiveness of teacher training in Basic Education; (b) need effective dissemination to public education networks; and (c) need to have validation for the functional progression of the teachers of the state education network, which demands specific agreement with this network of education, in order to be more attractive for the participation of this public, the research question was raised "Are there indications that ACIEPEs, in the context of teacher training, enhance the continuing teacher training promoted by UFSCar?" For the development of this work, which is configured as exploratory and of a qualitative and descriptive nature, the bibliographic research, the documentary analysis and the case study were carried out, using the semistructured interview as a central element for the collection of primary data. Data collection consists of two stages: (1) documentary analysis and (2) interviews with educational managers of public education networks in the city of São Carlos, SP; coordinators of ACIEPEs in the area of Mathematics Education in the Early Years, offered in the period from 2010 to 2014, at UFSCar - Campus São Carlos; and teachers working in the Early Years of Elementary School, who attended ACIEPE "Information Technology in the Training and Performance of Teachers Teaching Mathematics in the Early Years". A mapping of the ACIEPEs offered at UFSCar, from 2010 to 2014, was carried out in its four campuses, prioritizing a study of ACIEPEs focused on teacher training, focusing on those whose teachers were in the early years of the public school system. Municipality of São Carlos, SP. Next, the focus was focused on ACIEPEs in the area of mathematics education in the Early Years of Elementary School, culminating in the investigation of the contributions of ACIEPE "Information Technology in the Training and Performance of Teachers Teaching Mathematics in the Early Years" for professional development and the pedagogical practice of multipurpose teachers who attended it. The theoretical framework brings concepts of teacher training and training needs; presents models of continuing teacher training; a synthesis of the historical aspects and the problem of teacher education in the Brazilian context; and also the Center for Teacher Training and the institution responsible for the creation, implementation and offer of ACIEPEs.